Identification Of Solid Waste Management System In Household At Palembang City - Hendrik Jimmyanto; Imron Zahri; Hatta Dahlan (Program Pascasarjana Universitas Sriwijaya, 2017)
Increasing number of population give the impact of solid waste generation. Solid waste from household activity is about 55-80% of all waste in city which is composed of organic and inorganic waste. The important thing of solid waste management system is to know the characteristics of sources waste especially household as a step in improving solid waste management system in Palembang city. The aim of this study was to calculate solid waste generation of household in Palembang city and to identify composition and solid waste management system in household which has applied for along time. The research method is observation survey in 3 low income household dan 3 high income household respectively numbered 20. From the result will be analysis with statistic metode to see the relationship of the sampel using Anova one way. The amount of weight and volume of waste generation in low income household is 0.91 kg / person / day and 1.51 liters / person / day. The amount of the weight and volume of waste at high home income is 0.79 kg / person / day and 1.63 liters / person / day. In low income household produce more organic waste than high income household.